NILAI-NILAI PENDIDIKAN KEDISIPLINAN DALAM AL-QUR’AN SURAT AL-‘ASHR AYAT 1-3 MENURUT TAFSIR AL-MARAGHI - Palahudin, Palahudin; Daryaman, Daryaman; Hayatunnufus, Alifa Baiduri (Jurnal Penelitian Pendidikan Islam, 2016)
The purpose of this research is knowing the education value of discipline in Q.S Al-’Ashr vers 1-3 according to exegesis al-Maraghi. Research conclusion is as follows: 1 exegesis it Al-Qur’an an letter governor Al-’Ashr ayat 1-3 according to exegesis al-maraghi is as follows: a ) verse 1 a letter governor Al-’Ashr contains the importance of ( of meaning ) time in human life. b ) paragraph 2 contains men in a state losers, except those who allah kecualikan . c ) in paragraph 3 describes 3 way that must be done to avoid the including the losers, : believe and do good pious, each other told in truth and patience. 2 ) values education discipline in governor Q.S Al-’Ashr paragraph 1-3 according to exegesis al-maraghi is as follows: a ) discipline is a strong faith, that raises the urge to the intention use time. b ) the value discipline make a man has planing the future that will be taken, to have apparent aim and directed. c ) the principle discipline in the use of time spent effectively and efficiently minimize time not useful cause regret in the future. d) when embedded of the nature of discipline will appoint discipline to others one another told in truth and patience. 3 ) implication discipline nilai-nilai education in Q.S Al-’Ashr paragraph 1-3 is as follows: a ) intention discipline will cause me, peace, and comfort. B ) make planing so life would be clear and directed and the preparation. c ) discipline protected will assertive and success. d ) infuse discipline to others will spread of kedinamisan the trait of utilizing time, will many brothers thinking and much confidence in an effort to train himself virtuous, and will appear to be a movement trying to restore identity